Bt Resistance: Characterization and Strategies for GM Crops Producing Bacillus Thuringiensis Toxins 2015
DOI: 10.1079/9781780644370.0087
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cry1Ac resistance in cabbage loopers - a resistance mechanism selected in insect populations in an agricultural environment.

Abstract: Th e development of resistance to Bacillus thuringiensis (Bt) in insect populations in agriculture not only depends on the level of resistance conferred by a selected resistance mechanism, but also on the fi tness cost associated with the resistance mechanism under specifi c ecological and environmental conditions. Bt resistance in the cabbage looper (Trichoplusia ni), which was identifi ed by Janmaat and Myers (2003), is a case of Bt resistance evolved in an agricultural system, and is used in this chapter to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…4 ). ALPs are important Bt receptors in the midgut of Cry-susceptible insects ( Perera et al 2009 , Wang 2015 ). Two CBRs ( 95 R- 102 G and 257 N- 296 I) were reported to play essential roles in mediating interaction of Cry-binding ALPs with Cry toxins ( Fernandez et al 2009 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 ). ALPs are important Bt receptors in the midgut of Cry-susceptible insects ( Perera et al 2009 , Wang 2015 ). Two CBRs ( 95 R- 102 G and 257 N- 296 I) were reported to play essential roles in mediating interaction of Cry-binding ALPs with Cry toxins ( Fernandez et al 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cry-receptor interaction is necessary for Cry toxin insecticidal activities to occur. It was observed that the deletion of putative Cry-receptor binding sites or low expression of specific receptor protein could significantly reduce the susceptibility of susceptible insects to the related Cry toxins ( Wang 2015 ). In addition, reinstallation of the dysfunctional receptor-binding domains of the resistant insect strains could restore the toxin insecticidal activity against the previously resistant insects ( Badran et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation